Transport, fate, and toxicity of selected public health insecticides in waterways. Issue 1 (2nd January 2018) - Anderson, Jenise; Gitter, Anna; Lacey, Ronald; Karthikeyan, Raghupathy
ABSTRACT: Application of public health insecticides for mosquito control has increased dramatically with the recent outbreaks in the continental United States of dengue, chikungunya, and Zika. Mosquito control is often controversial because of the potential impacts on health and the environment due to the chemicals used. The emphasis in this review is to examine the transport, fate, and potential effects of the active ingredients in selected public health insecticides used for mosquito control. Due to the many potential entry points for insecticides, especially in urban areas where use is less monitored and application may be in greater amounts per unit area, this review suggests that a potential focus might be on the prevalence and quantification of the cumulative concentrations of these insecticides in natural systems. Often concentrations resulting from a single application are unlikely to cause mortality, but multiple applications may result in concentrations of environmental concern. Minimizing entrance to waterways and public water supply sources can be achieved by applying insecticides during prime meteorological conditions where drift and volatilization are minimized, using vegetated buffer zones in agricultural areas to prevent runoff, and avoiding application to impervious surfaces in urban areas.